2013
DOI: 10.1177/0022487113503871
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Teacher Entry Portals on Student Achievement

Abstract: The current teacher workforce is younger, less experienced, more likely to turnover, and more diverse in preparation experiences than the workforce of two decades ago. Research shows that inexperienced teachers are less effective, but we know little about the effectiveness of teachers with different types of preparation. In this study, we classify North Carolina public school teachers into portals—fixed and mutually exclusive categories that capture teachers’ formal preparation and qualifications upon first en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 37 publications
4
58
0
Order By: Relevance
“…Among studies using output-oriented approaches, evidence is mixed. Some have found meaningful differences between programs, suggesting that preparation can have significant effects on teachers' later performance (Henry, Purtell, et al, 2014;Boyd, Grossman, Lankford, Loeb, & Wyckoff, 2009;Gansle, Noell, & Burns, 2012). Using a school fixed effects (SFE) approach to examine all elementary programs that supply teachers to New York City schools, Boyd et al (2009) found differences between the average and the most effective programs to be 0.07 standard deviations in both math and English language arts (ELA).…”
Section: Introductionmentioning
confidence: 99%
“…Among studies using output-oriented approaches, evidence is mixed. Some have found meaningful differences between programs, suggesting that preparation can have significant effects on teachers' later performance (Henry, Purtell, et al, 2014;Boyd, Grossman, Lankford, Loeb, & Wyckoff, 2009;Gansle, Noell, & Burns, 2012). Using a school fixed effects (SFE) approach to examine all elementary programs that supply teachers to New York City schools, Boyd et al (2009) found differences between the average and the most effective programs to be 0.07 standard deviations in both math and English language arts (ELA).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the group identified holes within the program of study and recommended adding required courses or replacing topics within current courses. Recommendations to improve course offerings are consistent with literature where a review of several studies reported positive relationships between education coursework and teacher performance (Darling-Hammond, Berry, & Thoreson, 2001;Henry et al, 2014). The group also strongly recommended that the teacher educators work closely with content specialists both within and outside the institution, including specialists in the agriculture industry and in-service teachers, to make sure that there is a seamless flow from theory to real-life application.…”
Section: Conclusion and Recommendationsmentioning
confidence: 65%
“…Arguments in favor of ARL teachers tend to cite ARL teachers' content knowledge as a bi-product of industry experience, which the individual brings with them when they transition from the workforce to the classroom (Duncan & Ricketts, 2008;Fletcher, & Zirkle, 2011). Conversely, Henry et al (2014), argue that, although ARL programs offer an additional pathway and provide a means of alleviating the shortage of teachers, ARL teachers may be less-effective than their traditionally-prepared counterparts in certain subject areas.…”
Section: Arl Versus Traditionally-prepared Cte Teachersmentioning
confidence: 99%